On the periodic nature of some max-type difference equations. (13th September 2005) - Elabbasy, E. M.; El-Metwally, H.; Elsayed, E. M.
Abstract : We study some qualitative behavior of solutions of some max-type difference equations with periodic coefficients. Some new results of the periodicity character of solutions of that type of difference equations will be established.